Nhakanomics harvesting knowledge and value for re-generation through social innovation - Lessem, Ronnie; Mawere, Munyaradzi; Taranhike, Daud (Africa Talent Publishers, 2019)
Nhakanomics: Harvesting Knowledge and Value for Re-generation Through Social Innovation is a radical departure from the commonly held belief that neo-liberal economics from the US and the West is universal, and is the only solution to underdevelopment and poverty throughout the world. Instead, the book teases out and theorises the intellectually rutted terrain of development studies, and neo-liberal economics from a decolonial Pan-Africanist perspective. Following a path of social innovation, with perspectives drawn from social anthropology, economics, and business and management studies Nhakanomics is a unique socio-economic approach applicable in the Global South and in Southern Africa in particular. The study argues that the process and substance of nhakanomics with its pre-emphasis on the relational South provides a robust and holistic approach to social innovation and social transformation grounded in relational networks and 'meshworks'. The central idea is a call to re-GENE-rate society, through local Grounding and Origination, and tapping into local-global Emergent Foundations via a newly global Emancipatory Navigation, while ultimately culminating in global-local transformative Effects in four recursive cycles of re-GENE-rating C(K)umusha, Culture, Communication, and Capital after re-Constituting Africa-the 5Cs. With a novel and radical approach the book is an interrogation of neo-liberal economics in the Global South. As such, this book is remarkably handy to students and practitioners in the fields of economics, development studies, political science, science and technology studies, business management, sociology, transformation studies, and development related non-Governmental Organisations working with grassroots communities.
Keywords: Community development -- Africa, Southern.; Economic development -- Social aspects -- Africa, Southern.; Social systems.; Systèmes sociaux.; Développement communautaire -- Afrique australe.; Modern & contemporary fiction (post c 1945); BUSINESS & ECONOMICS / Development / Sustainable Development.; SOCIAL SCIENCE / Developing & Emerging Countries; Community development; Economic development -- Social aspects; Social systems; Southern Africa; Sozialer Wandel; Entwicklungsmodell; Alternative Wirtschaftspolitik; Subsaharisches Afrika